2015
DOI: 10.1021/bm5017173
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Behind the Stabilizing Action of Cellulose Nanofibrils in Wet-Stable Cellulose Foams

Abstract: The principal purpose of the investigation was to clarify the mechanisms behind the stabilizing action of cellulose nanofibrils (CNFs) in wet-stable cellulose foams. Following the basic theories for particle-stabilized foams, the investigation was focused on how the surface energy of the stabilizing CNF particles, their aspect ratio and charge density, and the concentration of CNF particles at the air-water interface affect the foam stability and the mechanical properties of a particle-stabilized air-liquid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
98
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 42 publications
5
98
0
Order By: Relevance
“…The efficiency of foam stabilization was attributed to the high aspect ratio 568 of the nanofibrils (∼2 µm × 3 nm), which facilitated the establishment of a robust gel-like 569 network between bubbles, as well as a large viscoelastic modulus at the particle-laden 570 air−water interface. Consistent with this explanation was the authors' observation that the 571 foam stability with the long fibrils was substantially greater than that with some shorter 572 cellulose nanocrystals (300 nm × 4 nm) of similar chemical composition and charge density 573 (Cervin et al, 2015). Another kind of cellulose-derived ingredient that appears suitable for 574 forming and stabilizing foams consists of charged colloidal particles ( Polysaccharide-based particles are not intrinsically surface-active: they usually require some 607 kind of hydrophobic modification in order to make them adhere to liquid interfaces.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The efficiency of foam stabilization was attributed to the high aspect ratio 568 of the nanofibrils (∼2 µm × 3 nm), which facilitated the establishment of a robust gel-like 569 network between bubbles, as well as a large viscoelastic modulus at the particle-laden 570 air−water interface. Consistent with this explanation was the authors' observation that the 571 foam stability with the long fibrils was substantially greater than that with some shorter 572 cellulose nanocrystals (300 nm × 4 nm) of similar chemical composition and charge density 573 (Cervin et al, 2015). Another kind of cellulose-derived ingredient that appears suitable for 574 forming and stabilizing foams consists of charged colloidal particles ( Polysaccharide-based particles are not intrinsically surface-active: they usually require some 607 kind of hydrophobic modification in order to make them adhere to liquid interfaces.…”
mentioning
confidence: 77%
“…Analogous rheological evidence for an emulsion-stabilizing network 558 by bacterial cellulose fibrils was reported by Paximada et al (2016). In yet further studies, Foam stabilization by nanofibrillated cellulose particles from wood pulp was investigated 564 by Cervin et al (2013Cervin et al ( , 2015. After the anionic nanofibrils had been hydrophobically 565 modified by adsorption of cationic octylamine, the particles exhibited significant surface 566 activity at the air-water interface, and they could make and stabilize foams at concentrations 567 as low as 0.5 wt%.…”
mentioning
confidence: 79%
“…Never‐dried pulp (60% Norwegian spruce and 40% Scots Pine) was kindly supplied by Domsjö Fabriker AB, Örnsköldsvik, Sweden. The CNF with a charge density of 600 μeq g −1 , a dry content of 0.89 wt%, width of 3–5 nm and length of about 500 nm, were prepared by TEMPO‐oxidation followed by high‐pressure homogenization on a Microfluidizer M‐110EH (Microfluidics Corp.) as described elsewhere .…”
Section: Methodsmentioning
confidence: 99%
“…To create a wet‐stable foam, that is, stabilize the air–water interface of dispersed bubbles, Gibbs stability criterion must be fulfilled, which states that the surface elasticity of the coating layer surrounding the air bubble must be equal and above half the surface tension of the liquid/suspension . In a previous study, it was shown that the slender cellulose nanofibres alone (as shown Figure a) do not fulfil this stability criterion, but by changing the surface energy of CNF, the migration of CNF to the air–water interface might be facilitated . The change in surface energy can be accomplished by for example adsorbing a surfactant onto the surface of CNF .…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] The amphiphilic properties were recently also used to stabilize the interface of oil in water emulsion via a Pickering stabilization. [21] In addition to the unique colloidal properties, [22] CNF has excellent mechanical properties, [12] oxygen barrier properties in the dry state [23] and a large surface area available for CNF-drug interaction.…”
Section: Introductionmentioning
confidence: 99%